2019
DOI: 10.11607/ijp.6072
|View full text |Cite
|
Sign up to set email alerts
|

General Health Quality of Life in Patients with Temporomandibular Disorders in a Population-Based Cross-Sectional Study in Southern Brazil

Abstract: Purpose: To assess the impact of temporomandibular disorders (TMD) on general health quality of life in a Brazilian population-based cross-sectional survey. Materials and Methods: A total of 1,643 patients were assessed using the World Health Organization Quality of Life Bref (WHOQOL-Bref) and the Research Diagnostic Criteria for Temporomandibular Disorders Axes I and II (RDC/TMD). Cross-tabulation of the data was carried out to compare TMD subjects to controls in all domains of the WHOQOL-Bref and the RDC/ TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Due to the high heterogeneity found here, it was necessary to use the random effect analysis, where the observed effect is an estimate of its real effect and follows a general distribution, with smaller studies gaining greater weight as compared to studies with larger sample sizes [47,48]. In order to improve future meta-analyses and to reduce heterogeneity and biases, we suggest that future studies apply either the RDC/TMD or DC/TMD axes I and II and standard quality of life measures in cases and controls, preferably from the general population, considering that only two studies in this review were population-based [16,26]. In addition, they should also report the size of the sample, the median, the standard deviation, not only for the entire TMD sample, but also for the RDC/TMD or DC/TMD axis I groups I, II and III.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the high heterogeneity found here, it was necessary to use the random effect analysis, where the observed effect is an estimate of its real effect and follows a general distribution, with smaller studies gaining greater weight as compared to studies with larger sample sizes [47,48]. In order to improve future meta-analyses and to reduce heterogeneity and biases, we suggest that future studies apply either the RDC/TMD or DC/TMD axes I and II and standard quality of life measures in cases and controls, preferably from the general population, considering that only two studies in this review were population-based [16,26]. In addition, they should also report the size of the sample, the median, the standard deviation, not only for the entire TMD sample, but also for the RDC/TMD or DC/TMD axis I groups I, II and III.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a direct relationship between both the duration of pain and pain intensity with poor quality of life in patients with TMD, showing that pain caused by TMD is one of the main reasons for the quality of life scores [6,[14][15][16][17]. Coherently, most articles clearly indicated that groups I and III, which have worse pain intensity, have worse quality of life as compared to group II of the RDC/TMD axis I [5,[18][19][20][21][22][23][24][25][26][27]. According to our results also, RDC/TMD axis I groups with higher pain levels (i.e., groups I and III) had worse quality of life as compared to the one with lower pain levels (i.e., group II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,[22][23][24] The intensity of pain and dysfunction caused by TMD has a negative impact on the general health quality of life of the population in the physical, social and environmental domains. 25 After DDRW treatment, the level of pain significantly decreased in both groups. This indicates that the patient could develop the physical movements related to TMJ without experiencing much pain, causing psychological comfort for daily activities.…”
Section: Ta B L E 2 Jaw Exercisesmentioning
confidence: 86%
“…The intensity of pain and dysfunction caused by TMD has a negative impact on the general health quality of life of the population in the physical, social and environmental domains 25 . After DDRW treatment, the level of pain significantly decreased in both groups.…”
Section: Discussionmentioning
confidence: 99%